Pengaruh Lama Tinggal terhadap Tingkat Partisipasi Masyarakat dalam Pengelolaan Lingkungan Permukiman - Wijaksono, Sigit (ComTech: Computer, Mathematics and Engineering Applications, 2013)
As the activities grow increasingly at Soekarno-hatta International Airport, the government in this case is PT Angkasa Pura needs to extend the airport by develop phase three in northern area of the existing airport. However, the expantion plan is opposed by the local goverment of Tangerang City because the plan may interfere with project of Tangerang Pantura Development Plan. For instead local goverment of Tangerang City proposes that the expantion would be build in the southern area. Obtaining the description of citizen attitude in this area is the aim of this study. This study is a descriptive research using a descriptive statistical analysis. Data collection using interviews with a questionnaire to respondends. By using Sherry Arnstein theory to measure the level of community participation. The analysis results indicated that the level of knowledge, awareness, and income levels affect the level of public participation in environmental management. Forms of participation provided most of the funds appropriated in the form of donations by income level.